2002
DOI: 10.1063/1.1508102
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and geometric structures of Co2Cn− and V2Cn−: Initial growth mechanisms of late and early 3d transition-metal carbide clusters

Abstract: Articles you may be interested inPhotoelectron spectroscopy of boron-gold alloy clusters and boron boronyl clusters: B3Au n − and B3(BO) n − (n = 1, 2) J. Chem. Phys. 139, 044308 (2013); 10.1063/1.4816010 Geometric and electronic factors in the rational design of transition-metal-centered boron molecular wheels J. Chem. Phys. 138, 134315 (2013); 10.1063/1.4798935Experimental and theoretical studies on the electronic properties of vanadium-benzene sandwich cluster anions, V n Bz n+1 − (n = 1-5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 40 publications
5
24
0
Order By: Relevance
“…The lowest-energy structure for FeC 2 has C 2v symmetry, which is in agreement with the previous theoretical calculations. 3,5,8 Analysis of the Mülliken population shows that 0.360e charge transfers from the Fe atom to the C atoms and that the magnetic moment, 2 B , lies primarily on the Fe atom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest-energy structure for FeC 2 has C 2v symmetry, which is in agreement with the previous theoretical calculations. 3,5,8 Analysis of the Mülliken population shows that 0.360e charge transfers from the Fe atom to the C atoms and that the magnetic moment, 2 B , lies primarily on the Fe atom.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the early 3d TMs ͑Ti, V, Cr͒ easily form large stable carbide clusters such as met-cars, while late 3d TMs ͑Co, Ni͒ have no such tendency. To explain the initial growth mechanisms of early and late 3d TM carbide clusters, Tono et al 3 measured photoelectron spectra of Co 2 C N ͑N =2,3͒ and V 2 C N ͑N =2-4͒ ions and deduced their electronic states and geometric structures by density functional theory ͑DFT͒. The growth mechanisms of the 3d transition-metal carbide clusters were discussed on the basis of the structural models obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, studies have found no difference between early and late 3d metals as regards the structures of monometallic di-and tri-carbides: MC 2 clusters (MϭSc, Ti, V, Fe, Co, and Ni͒ are isosceles triangles in the ground state, [11][12][13][14][15][16][17][18][19][20][21][22][23] and MC 3 clusters (MϭSc, Ti, V, Cr, Mn, Fe and Ni͒ have two-dimensional ''fan'' structures in which the M atom is bound to all three C atoms and the latter are bound together in a bent chain. 17,24 -26 Moreover, although in principle the early or late character of each M is expected to be more clearly manifested by dimetallic carbide clusters, extensive studies of M 2 C 2 clusters (MϭTi, V, and Co͒ using density-functional theory ͑DFT͒ have found no clear early-late difference: the ground-state geometries of V 2 C 2 and Co 2 C 2 , and the Ti 2 C 2 isomer of second-lowest energy, are all planar rings with transannular M-C bonds, [27][28][29] although ground-state Ti 2 C 2 is a planar ring with a transannular C-C bond. 29 However, recent experimental and DFT studies of Co 2 C 3 and V 2 C 3 by Tono et al 28 have shown that differences between early and late 3d metals are significant for M 2 C 3 , i.e., when the M/C proportion is the same as in met-cars, 1-7 whereas Co 2 C 3 has a C 2v -symmetric planar CoCCCCo-ring structure with a bent C 3 chain similar to free C 3 ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…1 The discovery of the novel metallocarbohedrene or "metcar" ͑M 8 C 12 + , M = Ti, V, Zr, Hf, and Nb͒ molecular cluster ions by Guo et al 2,3 in the early 1990s has prompted numerous studies on the growth and formation of these and the smaller transition-metal-carbon clusters that could be building blocks for the larger structures. 4 Mass spectrometric studies 5 suggested that MC 2 is a building unit, and subsequent experimental and theoretical work on small Ti n C m clusters has been motivated in part by the objective of learning more about the structure and bonding of this and other potential building blocks for the formation of titanium metallocarbohedrenes. 6 In an early theoretical study on small Ti n C m molecules using a linear combination of atomic orbitals molecular orbital approach, Reddy and Khanna 7 reported the structures for TiC, TiC 2 , Ti 2 C 2 , and Ti 2 C 3 .…”
Section: Introductionmentioning
confidence: 99%